Anti-dumping and countervailing procedures : use or abuse? : implications for developing countries - Neufeld, Inge Nora; United Nations Conference on Trade and Development; United Nations (New York : United Nations, 2001)
Analyzes antidumping and countervailing duty investigations, particularly as they impact developing countries. This study also scrutinizes WTO agreements and finds that many of the negative effects of antidumping and countervailing measures are not adequately addressed
'UNCTAD/ITCD/TAB/10'--T.p. verso
Includes bibliographical references (p. 29-31)
Keywords: World Trade Organization; Dumping (International trade); Antidumping duties